Design analysis of fixed-bed synergic adsorption of heavy metals and acid blue 25 on activated carbon. Issue 21 (2nd May 2016) - Hernandez-Eudave, M.T.; Bonilla-Petriciolet, A.; Moreno-Virgen, M.R.; Rojas-Mayorga, C.K.; Tovar-Gómez, R.
Abstract: This study reports the multicomponent adsorption of dye AB25, nickel (Ni 2+ ) and zinc (Zn 2+ ) ions on an activated carbon using binary mixtures of metal and dye, and packed bed columns at different operating conditions. Design parameters of packed bed adsorption columns have been calculated using the breakthrough curves and Thomas model, and an analysis has been performed to determine the effect and magnitude of the synergistic adsorption on the design parameters and adsorbent performance. Results showed that there is a strong synergistic adsorption of heavy metals on activated carbon caused by the presence of dye AB25 in binary mixtures. The magnitude of this synergistic adsorption effect depends on the dynamic operating conditions and type of heavy metal present in the binary system. The presence of dye AB25 in the binary mixtures caused a better degree of column utilization because the values of mass transfer zone decreased with respect to the results obtained with mono-component solutions. Metal adsorption capacities may increase up to 20 times if the binary mixture with dye AB25 is used as a column feed. In addition, the removal of heavy metal ions in adsorption columns packed with dye-loaded activated carbon is also an effective treatment process. This improvement in metal adsorption capacities is due to dye AB25 loaded in activated carbon may act as an additional active site for binding the metallic ions. In summary, this study showed that an adsorbent with a lower adsorption capacity for the removal of heavy metals can be employed, without comprising the process efficacy, in the treatment of multicomponent mixtures of dyes and heavy metals under dynamic operating conditions.